2019
DOI: 10.1017/s0144686x19000266
|View full text |Cite
|
Sign up to set email alerts
|

‘I will never be old’: adults with Down syndrome and their parents talk about ageing-related challenges

Abstract: AbstractThe life expectancy of people with Down syndrome (DS) has increased significantly over the last few decades. Consequently, they and their families face new ageing-related challenges, the first signs of which appear in people with DS around the age of 30. The goal of this study was to explore the perceptions of adults with DS regarding their own and their parents’ ageing and end of life, and to examine the views and concerns of the parents regarding the ageing of their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Three studies reported that the use of ICT by adults with DS resulted in a significant increase in their well-being, which was associated with autonomy and an improvement in perceptions of self-determination in everyday life, e.g., daily tasks, contact with family and friends, using useful apps, phone calendar, social media and setting up reminders [ 64 , 73 , 85 ]. Thirteen studies showed that the freedom to have their own rules, to live independently, and move out of home without the influence of their parents were paramount and considered a symbol of adulthood to adults with DS [ 62 64 , 68 , 74 , 76 , 88 , 90 , 91 , 93 , 95 , 97 , 98 ]. Five studies reported that some adults with DS demonstrated their ability to live independently such as catching a bus [ 93 ], taking responsibility for personal hygiene, house cleaning, laundry, cooking, paying bills, budgeting, taking medication and using public transport [ 63 , 64 , 97 ] and making decisions [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported that the use of ICT by adults with DS resulted in a significant increase in their well-being, which was associated with autonomy and an improvement in perceptions of self-determination in everyday life, e.g., daily tasks, contact with family and friends, using useful apps, phone calendar, social media and setting up reminders [ 64 , 73 , 85 ]. Thirteen studies showed that the freedom to have their own rules, to live independently, and move out of home without the influence of their parents were paramount and considered a symbol of adulthood to adults with DS [ 62 64 , 68 , 74 , 76 , 88 , 90 , 91 , 93 , 95 , 97 , 98 ]. Five studies reported that some adults with DS demonstrated their ability to live independently such as catching a bus [ 93 ], taking responsibility for personal hygiene, house cleaning, laundry, cooking, paying bills, budgeting, taking medication and using public transport [ 63 , 64 , 97 ] and making decisions [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies documented that regardless of the independence of adults with DS, some required support in going for walks, going to the cinema, staying healthy, seeing a doctor [ 63 , 98 ], emotional support [ 63 ], participation in extracurricular activities [ 95 ], personal care [ 74 , 100 ], handling money [ 88 , 100 ], respite care, using public transport [ 78 , 100 ] and want to continue living with parents [ 64 ]. In three studies, most adults with DS became more independent as they transitioned to adulthood and caregivers recognised the importance to their adults with DS QoL [ 91 , 96 , 98 ]; while one study documented that most mothers did not remember whether young adults with DS played an integral part of the transition process or were actively involved in decision making [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes of included studies were all relatively small and two stud- (Bibby, 2013;Finkelstein et al, 2020;Knox & Bigby, 2007), while an increasing number live in their own accommodation (Larson et al, 2017;Scottish Consortium for Learning Disabilities, 2022).…”
Section: Limitationsmentioning
confidence: 99%
“…While this included some people in supported living, the studies mainly featured people in residential or group homes. Many people with intellectual disability live with family members into old age supported by siblings or ageing parents (Bibby, 2013 ; Finkelstein et al, 2020 ; Knox & Bigby, 2007 ), while an increasing number live in their own accommodation (Larson et al, 2017 ; Scottish Consortium for Learning Disabilities, 2022 ). Thus, the majority of included studies do not reflect the experiences of people with intellectual disability and dementia living alone or those supported by family members.…”
Section: Limitationsmentioning
confidence: 99%
“…Nevertheless, 'successful ageing' of people with intellectual disabilities in Israel is still far from being achieved (Nissim, 2018). For example, parents of people with Down syndrome claim that the ageing of their children caught them unprepared (Finkelstein et al, 2019). A recent and thorough literature review found that research on older people with intellectual disabilities in Israel is comparatively scarce, and that descriptive data collected and published by governmental agencies regarding this population are insufficient (Tolub & Doron, 2020).…”
Section: Introductionmentioning
confidence: 99%